Chebyshev-Type Inequalities Involving (k, ψ)-Proportional Fractional Integral Operators. (21st June 2022) - Yewale, Bhagwat R.; Pachpatte, Deepak B.; Aljaaidi, Tariq A.
Abstract : Expanding the analytical aspect of mathematics enables researchers to study more cosmic phenomena, especially with regard to the applied sciences related to fractional calculus. In the present paper, we establish some Chebyshev-type inequalities in the case synchronous functions. In order to achieve our goals, we use k, ψ -proportional fractional integral operators. Moreover, we present some special cases.